Ergodic Theory, Dynamical Systems, and the Continuing Influence of John C. Oxtoby - Auslander, Joseph; Johnson, Aimee; Silva, Cesar E; Oxtoby, John C (Contemporary Mathematics, 2016)
This volume contains the proceedings of three conferences in Ergodic Theory and Symbolic Dynamics: the Oxtoby Centennial Conference, held from October 30-31, 2010, at Bryn Mawr College; the Williams Ergodic Theory Conference, held from July 27-29, 2012, at Williams College; and the AMS Special Session on Ergodic Theory and Symbolic Dynamics, held from January 17-18, 2014, in Baltimore, MD. This volume contains articles covering a variety of topics in measurable, symbolic and complex dynamics. It also includes a survey article on the life and work of John Oxtoby, providing a source of information about the many ways Oxtoby's work influenced mathematical thought in this and other fields.